A computational study of dicationic ionic liquids/CO₂ interfaces - Li, Song (Langmuir : the ACS journal of surfaces and colloids, 2015)
Recent studies on CO2 capture using dicationic ionic liquids (DILs) demonstrated that DILs are promising absorbents for CO2 uptake especially compared with monocationic ionic liquids (MILs) analogues, in which each cation carries single positive charge in contrast to two unit charges of a dication. However, DILs/CO2 interfacial properties at the molecular level are still unknown. This work investigated the CO2 absorption properties of representative DILs, 1-alkyl-3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide, [Cn(mim)2](Tf2N)2 (n = 3, 6, 12), using molecular dynamics (MD) simulations. The higher interfacial CO2 density at DIL than that at MIL interfaces suggests the increased CO2 interaction sites in DILs. The interfacial CO2 density also exhibits an alkyl chain length dependence which decreases with the elongation of alkyl chain and proportionally correlates with the content of fluorine atoms at interfaces. Different alkyl chain orientations in DILs were illustrated in contrast to those of MILs; both DILs and CO2 inside DILs exhibit lower diffusivity than MILs, in agreement with the stronger cation-anion binding energy of DILs. Moreover, DILs show a lower H2O and N2 uptake from flue gas compared with MILs, implicating the higher CO2/H2O and CO2/N2 selectivity